(untitled) (Journal of Comparative & International Higher Education, 2023)
The history of Boricuas on the archipelago is intertwined with the history of the institutions of learning. In the archipelago of Puerto Rico, public higher education faces challenges that include managing the aftermath of natural disasters, a global pandemic, and system-wide budget cuts. This study presents an opportunity to critically explore the complexities of the relationship between contemporary colonial contexts as framed by laws and policies, as well as larger aspects of coloniality through power hierarchies within public higher education. This study implemented qualitative inquiry through document analysis of government documents, University of Puerto Rico faculty generated documents, and campus-level documents. This research focuses on faculty-led spaces of decoloniality within pubic higher education.